ANALISIS REGRESI FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL PRODUKSI PADI DI INDONESIA BAGIAN BARAT - Jeni Marianti Loban (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2023)
This study aims to measure the influence of factors affecting rice production in the western part of Indonesia. Data analysis used multiple linear regression analysis, using the independent variable X1 = land area (Ha), X2 = rainfall (mm) and X3 = rainy days (days) on the dependent variable, namely the amount of rice production (Y). In this study, it was analyzed how much influence the land area (Ha), rainfall (mm), rainy days (days) had on the amount of rice production (tons). Data analysis using the help of RStudio software. The regression model obtained is Y=61.6+0.000007917X_1-0.1541X_2+0.0002555X_3 with a value of R2=0.9268.